Evidentiality in Philippine English and Filipino newspaper editorials - Dayag, Danilo T. (Philippine Journal of Linguistics, 2004)
This study examined the phenomenon of evidentiality in Filipino and Philippine English newspaper editorials. It aimed to (1) describe the sources of information or data (evidentials) found in Philippine English and Filipino newspaper, and (2) identify the strategies employed by these editorials in arranging the sources of information (evidentials) vis-a-vis the discourse structure of the texts. Data were taken from a one-month issue each of the three leading English-medium newspapers and of the three major morning tabloids circulated in the Philippines, or a total of 180 editorials (90 Philippine English and 90 Filipino editorials). The study found that Philippine English and Filipino newspaper editorials have more similarities to one another than differences. They are similar on the aspect of frequent use of more non-visual type of direct evidence than the visual type. On indirect evidentials, then is a widespread use of inferentials in newspaper editorials in both languages, compared to presumptives, perhaps in keeping with the interpretative and evaluative nature of editorials. A difference, however, can be noted in the use of mediated evidence (quotatives), namely, that, while it topped the list of mediated evidentials in editorials in both languages, reported speech is used more extensively in Philippine English editorials than in their Filipino counterpart. In addition, direct quotation is not fully exploited by Filipino editorials, in contrast to the Philippine English texts. Second, there is no predictable pattern in terms of the discourse position of evidentials in the Philippine newspaper editorials in that they can show up in any part of an editorial - beginning, middle or end part.